Use of Learning Model Cooperative Learning Type Team Games Tournament (TGT) to Improve Interpersonal Intellegence of Students in Social Studies Learning. - Subandi, Andi (International Journal Pedagogy of Social Studies, 2018)
The research was distributed by early observations in Class VII-5 Junior High School 1 Bandung. Observation results showed low interpersonal intelligence the learners that are happening in the learning process, problems that arise are: 1) the students who are less appreciative of other learners, 2) lack of healthy communication between learners, 3) lack of social sensitivity of the learners. To solve the problem of the study, researchers conducted a study class act with a design model Kemmis and McTaggart uses learning model cooperative learning-type team games tournament. This research was carried out through three cycles each cycle consisting of a single action. In the first Act, the study was conducted in two stages using intelligent game closely. The first Act shows the interpersonal intelligence in the category of "enough". In the second action, learning using games crossword puzzles. The second Act shows a significant incresase in interpersonal intelligence to the "good" category. In the third Act, learning to use the reverse-benar-salah games. The third Act shows an improvement to the "good" category, the majority of the three indicators of interpersonal intelligence shows the value of "good" so that researchers do not continue the action. As for the use of cooperative learning model summary of learning-type team games tournament in IPS can improve learning interpersonal intelligence of learners, suggestions for further research in order for researchers to be a benchmark in the interpersonal intelligence and research for teachers to use the student center learning model, so learning more fun and the material carried.